Genome-wide analysis of CHYR gene family and BnA03.CHYR.1 functional verification under salt stress in Brassica napus L. - Yanli Guo; Qingxiao Ren; Manman Song; Xiangxiang Zhang; Heping Wan; Fei Liu (BMC Plant Biology)
Abstract Brassica napus, an allotetraploid used as an oilseed crop, vegetable, or feed crop, possesses significant economic and medicinal value. Although the CHYR gene family has been functionally characterised in various aspects of plant growth, development, and stress responses, its systematic investigation in B. napus is lacking. In contrast to the seven CHYR genes (AtCHYR1-AtCHYR7) identified in Arabidopsis thaliana, nine CHYR orthologues were detected in B. rapa and B. oleracea, while 24 were found in B. napus. This discrepancy is consistent with the established triplication events that occurred during the Brassicaceae family evolution. Phylogenetic analysis indicated that the 24 CHYRs identified in B. napus could be categorised into three distinct groups. Among these, 24 BnCHYRs contained conserved domains, including the CHY-zinc finger, C3H2C3-type RING finger and zinc ribbon domains. Group III members featured an additional one to three hemerythrin domains in their N-terminal regions. Each BnCHYR group shared similar patterns in the distribution of conserved domains. Our results revealed that the selected eight BnCHYRs were up-regulated following heat treatment, exhibiting varying expression patterns in response to salt, cold, and drought stress during the seedling stage. Expression analysis revealed that several BnCHYRs were significantly induced by one or more abiotic stressors. BnA03.CHYR.1 was significantly induced by salt and heat stress and repressed by polyethylene glycol treatment. BnA03.CHYR.1 was localised in the nucleus and cytoplasm, and its overexpression in A. thaliana enhanced tolerance to salt stress. Our results provide a comprehensive analysis of the CHYR family in B. napus, elucidating the biological role of BnA03.CHYR.1 in adaptive responses of plants to salt stress.